PERAN SIGALOVADA SUTTA DALAM PENDIDIKAN KARAKTER REMAJA - Darma Handika Darma Handika (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2021)
This study examines the role of Sigalovada Sutta in adolescent character education. The impact of the current era of globalization has an impact on the character of teenagers. Problems that arise in the community such as violence perpetrated by teenagers, free sexual relations, destruction by students, fights between students, promiscuity, and drinking. The method used in compiling this research is a literature review to obtain information data by utilizing existing facilities in the library, as well as other sources. The results of this study are to shape the character and personality of adolescents to be better and easier to adapt to the environment, namely by providing an understanding of the character values ​​contained in the Sigalovada Sutta and education contained in the Sigalovada Sutta.